2007
DOI: 10.1177/172460080702200103
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Elevation of Serum Alpha Fetoprotein in Decompensated Cirrhosis without Hcc: an Ominous Sign

Abstract: Three cases of extreme elevation of serum alpha fetoprotein (>10,000 ng/mL) with decompensated cirrhosis without demonstrable hepatocellular carcinoma are reported. While 2 patients died of liver failure, 1 survived after liver transplantation. Extreme elevation of alpha fetoprotein not associated with hepatocellular carcinoma in liver cirrhosis heralds an ominous prognosis necessitating urgent liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Alpha-fetoprotein has been shown to be a marker of hepatic compromise in patients in the absence of malignancy. 3,4 This phenomenon has been described in the literature and confirmed with resolution of the tumor marker over time in our patient. Over the next 3 months, the value returned to normal, at 169.2 mg/L (Table 1).…”
Section: Discussionsupporting
confidence: 84%
“…Alpha-fetoprotein has been shown to be a marker of hepatic compromise in patients in the absence of malignancy. 3,4 This phenomenon has been described in the literature and confirmed with resolution of the tumor marker over time in our patient. Over the next 3 months, the value returned to normal, at 169.2 mg/L (Table 1).…”
Section: Discussionsupporting
confidence: 84%
“…Typically, it is associated with cholangiocarcinoma and used to differentiate between cholangiocarcinoma and HCC (Senturk and Cumali, 2007). However, PTHrP has been found in the fetal liver, but is typically not present in adults (Senturk and Cumali, 2007). While studies have been reported of AFP levels greater than 10,000 pg/ml without any sign of carcinoma, our patient demonstrated significantly higher levels with hypercalcemia (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 57%
“…Our patient had a rare case of HCC with extremely elevated AFP levels and elevated PTHrP leading to hypercalcemia. In the setting of hypercalcemia of malignancy, it is important to differentiate if there is hypercalcemia due to bony metastasis or if it is due to PTHrP (Senturk and Cumali, 2007). PTHrP has demonstrated a significant role in hypercalcemia of malignancy (Wang and Zhang, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations